PENINGKATAN KETERAMPILAN BERBAHASA INGGRIS SISWA MELALUI MODEL PEMBELAJARAN COOPERATIVE SCRIPT DI KELAS VIII-6 SMP NEGERI 1 TIGAPANAH - Rahel Br Sitepu (Universitas Negeri Medan, 2019)
Abstract: Improving Students' English Language Skills Through Cooperative Script Learning Models in Class VIII-6 Middle School 1 Tigapanah. This study aims to determine the improvement of students' English learning skills and activities using cooperative script learning models. The results showed that; 1) the students' English skills improved in formative I and formative II showing completeness of 74% and 88% and experiencing a 14% increase in classical ; 2) English learning activities of students increased by applying cooperative script learning models from cycle I to cycle II including reading and studying material from 61.76% on sufficient criteria to 84.93% on good criteria, listening activities of teachers reading text from 61, 76% on sufficient criteria to 81.62% on good criteria, the activity of practicing identifying information in the text from 62.50% on the sufficient criteria to be 86.03% on the good criteria, the activity of expressing the text verbally from 61.03% on the sufficient criteria to 78.68% in good criteria. The activity concluded the subject matter from 61.03% on sufficient criteria to 78.31% in good criteria.Keywords: Cooperative Script, English Language SkillsAbstrak: Peningkatan Keterampilan Berbahasa Inggris Siswa Melalui Model Pembelajaran Cooperative Script di Kelas VIII-6 SMP Negeri 1 Tigapanah. Penelitian ini bertujuan untuk mengetahui peningkatan keterampilan dan aktivitas belajar bahasa Inggris siswa menggunakan model pembelajaran cooperative script. Hasil penelitian menunjukkan bahwa; 1) keterampilan berbahasa Inggris siswa meningkat pada formatif I dan formatif II menunjukkan ketuntasan sebesar 74% dan 88% dan mengalami peningkatan 14% secara klasikal; 2) aktivitas belajar bahasa Inggris siswa meningkat dengan menerapkan model pembelajaran cooperative script dari siklus I ke siklus II diantaranya membaca dan mempelajari materi dari 61,76% pada kriteria cukup menjadi 84,93% pada kriteria baik, aktivitas mendengarkan guru membaca teks dari 61,76% pada kriteria cukup menjadi 81,62% pada kriteria baik, aktivitas berlatih mengidentifikasi informasi dalam teks dari 62,50% pada kriteria cukup menjadi 86,03% pada kriteria baik, aktivitas mengungkapkan teks secara lisan dari 61,03% pada kriteria cukup menjadi 78,68% pada kriteria baik. Aktivitas menyimpulkan materi pelajaran dari 61,03% pada krieria cukup menjadi 78,31% pada krieria baik.Kata Kunci : Cooperative Script, Keterampilan Berbahasa Inggris